Molecular characterization of Omp31 gene of Indian field Isolates of Brucella melitensis - RAJAGUNALAN, S; KUMARI, GITA; GUPTA, S K; KUMAR, ASHOK; AGARWAL, R K; RAWOOL, D B; SINGH, D K (The Indian Journal of Animal Sciences, 2013)
PCR amplification and sequencing of Omp31 gene of 19 Indian field isolates of Brucella melitensis was performed. The sequence analysis revealed that all 19 isolated had 100% nucleotide sequence identity confirming the fact that the Omp31 gene of B. melitensis is highly conserved and stable. The amino acid sequences also revealed 100% sequence homology with published sequences. The protein structure predicted using the amino acid sequences confirms that this porin protein consists of 8 Beta barrels and 3 surface exposed loop portions.